2018
DOI: 10.1002/adsc.201701641
|View full text |Cite
|
Sign up to set email alerts
|

Lewis‐acid Promoted Chemoselective Condensation of 2‐Aminobenzimidazoles or 3‐Aminoindazoles with 3‐Ethoxycyclobutanones to Construct Fused Nitrogen heterocycles

Abstract: A Lewis-acid promoted chemoselective condensation of 2-aminobenzimidazoles or 3-aminoindazoles with 3-ethoxycyclobutanones is presented. Diverse fused heterocycles benzo[4,5]-imidazo[1,2-a]pyrimidine and pyrimido[1,2-b]-indazole derivatives were obtained in moderate to high yields under mild conditions, the reaction mechanism of which was in sharp contrast to previous [3 + 3] annulation reaction of 3-ethoxycyclobutanones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In addition, it was noted that the developed approach can be easily scaled without decrease of the yield of the target products (Scheme 20). 63 The above approach to the construction of the pyrimidobenzimidazole structure using cyclic ketones is not the only example of the use of this kind of carbonyl compounds. Thus, a group of Chinese researchers used squaraic acid chloride (67) in the synthesis of a series of alkyl 2-chloropyrimido[1,2-a]benzimidazole-3-carboxylates 68a-g (Scheme 21).…”
Section: Scheme 18mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was noted that the developed approach can be easily scaled without decrease of the yield of the target products (Scheme 20). 63 The above approach to the construction of the pyrimidobenzimidazole structure using cyclic ketones is not the only example of the use of this kind of carbonyl compounds. Thus, a group of Chinese researchers used squaraic acid chloride (67) in the synthesis of a series of alkyl 2-chloropyrimido[1,2-a]benzimidazole-3-carboxylates 68a-g (Scheme 21).…”
Section: Scheme 18mentioning
confidence: 99%
“…In addition, it was noted that the developed approach can be easily scaled without decrease of the yield of the target products (Scheme 20 ). 63
Scheme 20
…”
Section: The Reaction Of Aminobenzimidazoles With Bifunctional Synthetic Equivalentsmentioning
confidence: 99%
“…[9] Alternatively, Song et al demonstrated a chemoselective condensation of 3-aminoindazoles with 3-ethoxycyclobutanones promoted by a Lewis acid (Scheme 1a). [10] Gao reported an NH 4 I-promoted multi-component oxidation of 3aminoindazoles, aromatic aldehydes and triethylamine (Scheme 1b). [11] However, these strategies only gave 4substituted pyrimido [1,2-b]indazoles.…”
Section: Introductionmentioning
confidence: 99%
“…[9 -11] The synthesis of fused pyrimidines is very interesting for the fusion of biodynamic heterosystems. [12,13] This has proved very useful in developing new molecular structures for drug candidates with different pharmacological activities. Pyrimidine-fused scaffolds are an area of heterocyclic chemistry research that is rapidly expanding.…”
Section: Introductionmentioning
confidence: 99%